THE EFFECT OF CIRC STRATEGY AND ACHIEVEMENT MOTIVATION TOWARD STUDENTS/' READING COMPREHENSION - ., LELA RAHMAWATI; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Dr.Ni Made Ratminingsih, MA (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2014)
The aim of this study is to investigate (1) whether there is a difference in the reading comprehension between students who are taught by using CIRC strategy and those taught by using the conventional strategy; (2) an interactional effect between the reading strategyi applied and achievement motivation toward students? reading comprehension; (3) a difference in reading comprehension between students with high achievement motivation who are taught by using CIRC strategy and those taught by using the conventional strategy; and (4) a difference in reading comprehension between students with low achievement motivation who are taught by using CIRC strategy and those taught by using the conventional strategy. The study administrated a 2X2 factorial design, which 175 students were involved as the sample. The data were collected by using qquestionnaire and a reading test then analyzed by Two-way ANOVA. The result indicates that (1) there is a significant difference in reading comprehension between the students who are taught by using CIRC strategy and those taught by using the conventional strategy; (2) there is an effect of the interaction between the teaching strategy applied and students? achievement motivation toward their reading comprehension; (3) there is a significant difference in reading comprehension between students with high achievement motivation who are taught by using CIRC strategy and those taught with the conventional strategy; and (4) there was significant difference in reading comprehension between the students with low achievement motivation who are taught by using CIRC strategy and those taught with the conventional strategy.Kata Kunci : : CIRC, achievement motivation, reading comprehension The aim of this study is to investigate (1) whether there is a difference in the reading comprehension between students who are taught by using CIRC strategy and those taught by using the conventional strategy; (2) an interactional effect between the reading strategyi applied and achievement motivation toward students? reading comprehension; (3) a difference in reading comprehension between students with high achievement motivation who are taught by using CIRC strategy and those taught by using the conventional strategy; and (4) a difference in reading comprehension between students with low achievement motivation who are taught by using CIRC strategy and those taught by using the conventional strategy. The study administrated a 2X2 factorial design, which 175 students were involved as the sample. The data were collected by using qquestionnaire and a reading test then analyzed by Two-way ANOVA. The result indicates that (1) there is a significant difference in reading comprehension between the students who are taught by using CIRC strategy and those taught by using the conventional strategy; (2) there is an effect of the interaction between the teaching strategy applied and students? achievement motivation toward their reading comprehension; (3) there is a significant difference in reading comprehension between students with high achievement motivation who are taught by using CIRC strategy and those taught with the conventional strategy; and (4) there was significant difference in reading comprehension between the students with low achievement motivation who are taught by using CIRC strategy and those taught with the conventional strategy.keyword : CIRC, achievement motivation, reading comprehension